(untitled) (Gestão & Regionalidade, 2016)
The discussion about innovation practices that seek to ensure long-term competitive strategies and incorporate environmental values has been increasing in academic debates. In this sense, the term ecoinnovation has been established as a consistent theoretical concept and has the potential to reconcile environmental and economic objectives. Thus, this study proposes a conceptual model of evaluation of the determining factors for ecoinnovation. Therefore, five external and three internal dimensions that can influence the process of ecoinnovation in enterprises were identified based on literature review. This analytical model applied in a case study showed the importance of internal factors such: the profile of the entrepreneur leadership and intermediate level managers. As for external factors, the participation in collaborative networks and the ability to meet regulatory frameworks are highlighted. The contribution of the study, therefore, is to present the conceptual model of evaluation to support future studies on this theme.